Active Directory Field Guide - Hunter, Beau (Apress : Imprint: Apress, 2005)
Active Directory Field Guide is ideal for Windows and Active Directory administrators and consultants. It contains valuable descriptions of higher-level skills, tasks, and tools, including migration, large-scale deployment, security, and disaster recovery, and provides bold, nontraditional solutions. Author Laura E. Hunter is a Microsoft "Most Valuable Professional," and this book is based on her real-world knowledge. It will help you save time and increase your network efficiency. Full of task-based, advanced solutions, it will also function as an indispensable reference guide.